A modified dinucleotide motif specifies tRNA recognition by TLR7 - Kaiser, Steffen; Rimbach, Katharina; Eigenbrod, Tatjana; Dalpke, Alexander; Helm, Mark (RNA, 2014)
RNA can function as a pathogen-associated molecular pattern (PAMP) whose recognition by the innate immune system alerts the body to an impending microbial infection. The recognition of tRNA as either self or nonself RNA by TLR7 depends on its modification patterns. In particular, it is known that the presence of a ribose methylated guanosine at position 18, which is overrepresented in self-RNA, antagonizes an immune response. Here, we report that recognition extends to the next downstream nucleotide and the effectively recognized molecular detail is actually a methylated dinucleotide. The most efficient nucleobases combination of this motif includes two purines, while pyrimidines diminish the effect of ribose methylation. The constraints of this motif stay intact when transposed to other parts of the tRNA. The results argue against a fixed orientation of the tRNA during interaction with TLR7 and, rather, suggest a processive type of inspection.
Gesehen am 18.09.2020